1997
DOI: 10.1128/aem.63.1.329-331.1997
|View full text |Cite
|
Sign up to set email alerts
|

Nylon biodegradation by lignin-degrading fungi

Abstract: The biodegradation of nylon by lignin-degrading fungi was investigated. The fungus IZU-154 significantly degraded nylon-66 membrane under ligninolytic conditions. Nuclear magnetic resonance analysis showed that four end groups, CHO, NHCHO, CH 3 , and CONH 2 , were formed in the biodegraded nylon-66 membranes, suggesting that nylon-66 was degraded oxidatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…However, degradation of BPA and NP by microorganisms other than bacteria has not yet been attempted. There is currently great interest in the lignin-degrading fungi and ligninolytic enzymes because their industrial potentials are recognized in biomechanical pulping (Kashino et al, 1993), biobleaching (Paice et al, 1993;Katagiri et al, 1995;Ehara et al, 1997), and degradation and detoxification of recalcitrant environmental pollutants such as dioxins (Bumpus et al, 1985), chlorophenols (Joshi and Gold, 1993), nylon (Deguchi et al, 1997;Deguchi et al, 1998), polyethylene (Iiyoshi et al, 1998;Ehara et al, 2000), and dyes (Ollikka et al, 1993;Nishida et al, 1999). It has been demonstrated that laccase, manganese peroxidase (MnP), and/or lignin peroxidase (LiP) producedc extracellularly by lignin-degrading fungi are involved in the degradation of lignin and these pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…However, degradation of BPA and NP by microorganisms other than bacteria has not yet been attempted. There is currently great interest in the lignin-degrading fungi and ligninolytic enzymes because their industrial potentials are recognized in biomechanical pulping (Kashino et al, 1993), biobleaching (Paice et al, 1993;Katagiri et al, 1995;Ehara et al, 1997), and degradation and detoxification of recalcitrant environmental pollutants such as dioxins (Bumpus et al, 1985), chlorophenols (Joshi and Gold, 1993), nylon (Deguchi et al, 1997;Deguchi et al, 1998), polyethylene (Iiyoshi et al, 1998;Ehara et al, 2000), and dyes (Ollikka et al, 1993;Nishida et al, 1999). It has been demonstrated that laccase, manganese peroxidase (MnP), and/or lignin peroxidase (LiP) producedc extracellularly by lignin-degrading fungi are involved in the degradation of lignin and these pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Because the material was to be analyzed by several properties, the sample Although they are considered nonbiodegrading microorganisms, soil fungi such as Aspergillus fumigatus, Aspergillus terreus, and Fusarium solani have been reported to degrade synthetic polymers, especially by stimulating other microbial communities. [35][36][37][38][39] However, additional factors or a limited carbon source are prerequisites for stimulating microbial communities. Mycelia growing over neat mPE were not observed, indicating that the Motierella elongata fungus responsible for the degradation of the plastic samples was not degrading mPE but was degrading the organic component of the blend.…”
Section: Identification Of the Fungus Growing Over The Plastic Samplesmentioning
confidence: 99%
“…This confirms that protease catalyse hydrolysis of polyamide chains produces fibre with more functional groups and, as a consequence, improves the susceptibility of acid dye attraction. Further hydrolysis is shown with an increase in the enzyme concentration [32,38,39].…”
Section: Structural Informationmentioning
confidence: 99%
“…Many research papers have been published on the surface hydrolysis of polyester using enzymes and its dyeing behaviour [32,[35][36][37], but few have reported on the dyeing of hydrolysed polyamide. Studies have shown that enzymatic hydrolysis can be achieved on nylon oligomers [38][39][40][41][42]. Other experiments have shown that the surface of nylon 66 and nylon 6 can be modified by oxidative enzymes without reducing the fibre diameter [43].…”
Section: Introductionmentioning
confidence: 99%